2008
DOI: 10.1111/j.1365-313x.2008.03518.x
|View full text |Cite
|
Sign up to set email alerts
|

Glycine‐rich RNA‐binding protein7 affects abiotic stress responses by regulating stomata opening and closing inArabidopsis thaliana

Abstract: SummaryDespite the fact that glycine-rich RNA-binding proteins (GRPs) have been implicated in the responses of plants to environmental stresses, their physiological functions and mechanisms of action in stress responses remain largely unknown. Here, we assessed the functional roles of GRP7, one of the eight GRP family members in Arabidopsis thaliana, on seed germination, seedling growth, and stress tolerance under high salinity, drought, or cold stress conditions. The transgenic Arabidopsis plants overexpressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
215
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 274 publications
(232 citation statements)
references
References 51 publications
11
215
1
Order By: Relevance
“…These proteins are expressed abundantly in the guard cells and have been implicated in the control of stomata opening and closing (Kim et al, 2008). AtGR-RBP expression is induced by DREB1A (Maruyama et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…These proteins are expressed abundantly in the guard cells and have been implicated in the control of stomata opening and closing (Kim et al, 2008). AtGR-RBP expression is induced by DREB1A (Maruyama et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…ABH1/CBP80 and CBP20 contribute to the regulation of AS and preferentially affect AS of the first intron, particularly at the 59 splice site (Laubinger et al, 2008;Raczynska et al, 2010). The hnRNP-like At-GRP7 (for glycine-rich RNA binding protein 7) that is upregulated by cold and oxidative stress has also been associated with ABA responses (Carpenter et al, 1994;Cao et al, 2006;Kim et al, 2008;Schöning et al, 2008;Schmidt et al, 2010;Streitner et al, 2010). GRP7 regulates a number of AS events, in particular those involving alternative 59 splice sites.…”
Section: Function Of Sfs In Abiotic Stress Responsementioning
confidence: 99%
“…Glycine-rich RNA binding protein 7 (GRP7) is modulated by the circadian clock and in response to various environmental stresses, including cold (Heintzen et al, 1997;Kim et al, 2008). Interestingly, this protein is highly expressed in guard cells, regulates stomatal opening and closing in response to stress (Kim et al, 2008), and was recently shown to be an ADPribosylation target for a type III Pst DC3000 effector, hopU1 (Fu et al, 2007).…”
Section: Is There Circadian Regulation Of Immunity In Plants?mentioning
confidence: 99%
“…Interestingly, this protein is highly expressed in guard cells, regulates stomatal opening and closing in response to stress (Kim et al, 2008), and was recently shown to be an ADPribosylation target for a type III Pst DC3000 effector, hopU1 (Fu et al, 2007). Arabidopsis plants deficient in GRP7 due to insertional mutagenesis were more susceptible to Pst DC3000 infection that wild-type plants (Fu et al, 2007).…”
Section: Is There Circadian Regulation Of Immunity In Plants?mentioning
confidence: 99%
See 1 more Smart Citation